IDENTIFICAÇÃO DE BOAS PRÁTICAS QUE CONTRIBUEM PARA A DIMINUIÇÃO DA VARIABILIDADE DOS PROCESSOS - Cruz, Herbert Melo; Santos, Débora de Gois (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
One of the major challenges faced by construction management is the implementation of activities within schedule, because variability frequently. This research study aims to identify the best practices that contribute to reduce processes variability. The methodology consisted of direct observations with nine construction sites visited. The study analyzed reinforced concrete works (conventional), structural masonry and concrete walls cast on-site. The results showed that 21 best practices were raised in the construction sites and they were relationship with reduction of 42% of the causes of variability. The study also showed deficiencies, on the part of managers, to deal with the impacts of process variability. The best practices are shown as an alternative to reduce the impacts and consequences of this specific type of variability, but still inefficiently. The results were part of Master's dissertation whose theme refers to the analysis of the causes of process variability in different construction systems.